A six-chamber medium-to-high temperature refrigeration system for laboratory purposes - Belaid, Ashur Belaid (Cape Peninsula University of Technology, 2017)
Thesis (MTech (Mechanical Engineering))--Cape Peninsula University of Technology, 2017. === Food and water fuel and sustain life on earth. Since ancient times, their sourcing and preservation have been very important issues to humanity. In modern times, experimentation is a major step in analysing how cold storage problems in the medical and food science technology fields can be addressed. For investigating spoilage of new products and/or growth of pathogens in such cases, it is necessary to do experiments at different low temperatures for prolonged periods and check the effects. While this can be undertaken in a conventional two chambers fridge, it takes a long time to investigate a whole range of feasible storage temperatures. This dissertation describes work intended to treble the samples in such investigations and, therefore, significantly reduce the times. Six well- insulated chambers were constructed from plastic and wood and set at different temperatures. An ordinary deep freezer was used as the main heat sink for the chambers. Experiments were done with different methods to get the best result for the cold air flow into the chambers over period of eight months. The chambers temperatures were set between 0 and 15°C. It was finally established that a properly-designed six-chamber system could successfully be added to an ordinary freezer to provide different medium-to-high refrigeration temperatures without the use of a multi-pressure refrigeration cycle.